Significant caries and the interactive effects of maternal‐related oral hygiene factors in urban preschool children. (10th November 2016) - Lin, Ying‐Chun; Wang, Wen‐Chen; Chen, Jen‐Hao; Chen, Ping‐Ho; Lee, Chien‐Hung; Huang, Hsiao‐Ling
Abstract: Objectives: This study examined significant caries (SiC) and the interactive effects of maternal‐related oral hygiene factors in urban preschool children. Methods: A cross‐sectional study was designed to collect data from a cluster of randomly selected samples in 2011. A total of 495 child‐mother pairs from the San‐Ming District of Kaohsiung City, Taiwan, participated in the study. Children aged 4‐6 years received dental examinations, and their mothers completed a self‐administered questionnaire. The SiC Index indicated the highest caries values in participants. The association between 3 groups – dmft (decayed, missing, and filled teeth)‐free, non‐SiC, and SiC – and the mothers' and their children's factors were examined using polytomous logistic regression analysis. Results: Among the SiC children, caries experience was most frequent in the mandibular molars (64.5‐84.9 percent), and almost 50 percent of these children had central incisor caries. The significant factors associated with the SiC children were lower maternal self‐efficacy in oral hygiene [adjusted odds ratio (aOR) = 2.04], child's intake of sugar‐sweetened beverages (SSBs) more than once per day (aOR = 2.27), and irregular child dental checkups (aOR = 2.32). Significant interaction effects were detected among children who received irregular dental checkups and whose SSBs intake was more than once per day and whose mothers had lower self‐efficacy in oral hygiene ( P for interaction term = 0.034 and 0.004, respectively). Conclusions: Caries prevention programs should prioritize enhancing maternal self‐efficacy in oral hygiene and emphasize childhood SSBs intake management and regular dental checkups to mothers to prevent severe caries in preschool‐aged children.